Understanding Music and Nonviolence Through Understanding Music and Violence - Robertson, Craig (Thammasat Review, 2015)
NGOs and other benefactors have long used musical activity as part of a peacebuilding or development strategy, believing that music brings people together, heals traumas and promotes peace, yet there is scant empirical evidence to support this notion. At the very least, musical activity is usually considered to be a nonviolent endeavour yet there is evidence that contradicts even this. Drawing on a synthesis of sociological, musicological and conflict theory, this paper attempts to explain how the same physical phenomenon can produce such wildly different results, beliefs and behaviours through the musical interaction with personal and social belief systems, identities, memories and emotions. Keywords: Music Sociology, Conflict, South East Asia, Peacebuilding